Stem cells. from basic research to therapy - Calegari, Federico; Waskow, Claudia (Stem Cells., 2014)
The first volume of Stem Cells deals with the fundamental principles that govern embryonic and somatic stem cell biology. Historically, the identification and characterization of such pathways and general rules of stemness occurred during embryonic development and Volume I reflects this with topics spanning cell cycle regulation, epigenetics, and asymmetric cell division in a number of organ systems from planarian to human. Three specific sections discuss i) Basic Stem Cell Biology, ii) Tissue Formation During Development, and iii) Model Organisms with particular emphasis on t.